Difference in neonatal hemoglobin levels between delayed and direct umbilical clamping - Dwi Rahmawati; Devi Arista; Yesi Mustikasari; Niki Astria; Gustien Siahaan; Dewi Riastawati (Faculty of Nursing Universitas Padjadjaran, 2026)
Introduction: Anemia is globally considered a public health problem due to its adverse impact on physical, cognitive, motor, and behavioral development during infancy and childhood. The prevalence of anemia in the first year of life reaches 50%. Procedures that can be performed during childbirth to increase the iron stores of newborns and contribute to the prevention of anemia by delaying cord cutting. Methods: This study was a quantitative study with a quasi-experimental Posttest Only Control Group Design with an uneven control group. The research was conducted in the Lubuk Kambing Health Center Working Area in February-March 2024 with a total sample of 40 full-term babies who were selected using the total sampling technique and divided into intervention groups (delayed cord clamping) and control (immediate clamping). Data analysis used the Mann-Whitney U test with a 95% confidence level (α = 0.05). Results: The average hemoglobin level performed by Delay Cord Clamping was 17.3 g/dl with a minimum value of 12.5 and a maximum value of 21.4 g/dL and that not performed by Delay Cord Clamping was 15.3 g/dl with a minimum value of 13.5 and a maximum of 19.2 g/dL. The results of the statistical test showed a p value of 0.007 <0.05 which means that there is a significant difference in hemoglobin between Delay Cord Clamping and no Delay Cord Clamping. Conclusion: Delayed cord clamping has a significant effect on increased neonatal hemoglobin levels. These findings confirm that delayed cord clamping practices can be integrated as part of obstetric and nursing care standards in normal childbirth to support the prevention of anemia from an early age. Nurses and midwives play a role in implementing these evidence-based procedures, conducting antenatal education for pregnant women, and ensuring optimal monitoring of neonatal conditions to improve the quality of maternal and neonatal services.